Predictors of changes in daily alcohol consumption in the aftermath of military deployment. (1st February 2015) - Trautmann, S.; Schönfeld, S.; Behrendt, S.; Heinrich, A.; Höfler, M.; Siegel, S.; Zimmermann, P.; Wittchen, H.-U.
Highlights: Aim: prediction of courses in alcohol use following military deployment. Several distal and proximal factors are related to increased alcohol use. Low post-traumatic stress disorder (PTSD) symptom severity and few adverse childhood experience predict decreased alcohol use. There are differential predictors and correlates of decreased and increased alcohol use. Findings could stimulate research on mechanisms underlying trajectories of alcohol use following stressful experiences. Abstract: Background: Several studies have documented factors related to increase in alcohol consumption in the context of stressful experiences. However, little is known about predictors of different courses of alcohol use in this context. This study aims to investigate diverse predictors and correlates of increase and decrease of average daily alcohol consumption (aDAC) in the aftermath of military deployment taking into account a variety of potentially relevant factors. Methods: N = 358 soldiers were examined before (T1) and 12 months after return from deployment (T2) using standardized interviews. Change in aDAC was categorized into decreased ( n = 72), stable ( n = 215) and increased ( n = 71) aDAC. Results: Overall, aDAC did not change significantly between T1 and T2 (median change = 0.0 g, inter quartile range = 11.3 g). Compared to stable aDAC, increase was characterized by a lower proportion of high-educated individuals (OR: 0.3 (0.1–0.7), p = 0.008), lower rank (marginally significant: OR: 2.0 (1.0–4.1), p = 0.050), and less acceptance (trend: MR: 0.97 (0.93–1.00), p = 0.053). Correlates of increased aDAC were less social support (MR: 0.84 (0.71–0.99), p = 0.043), more sleeping problems (MR: 1.15 (1.00–1.31), p = 0.045) and more negative post-event cognitions following deployment (MR: 2.32 (1.28–4.21), p = 0.006). Decrease in aDAC was predicted by lower PTSD symptom severity before deployment (MR: 0.34 (0.16–0.72), p = 0.005) and less childhood emotional neglect (marginally significant: MR: 0.78 (0.60–1.00), p = 0.050). Conclusions: Increase and decrease in alcohol use after stressful experiences might have differential risk factors and correlates. Findings might stimulate future research that could result in improved measures to prevent increases as well as in interventions that could foster decreases in alcohol consumption in the context of stressful experiences.